Knowledge Building on Climate Change among Women in Flood-Prone Communities in Cotabato City - Gayak, Estelita (JPAIR Multidisciplinary Research, 2018)
According to the United Nations (UN), disaster situations such as flooding in South and East Asia are increasingly linked to climate change, and the greater vulnerability of women is most striking. Women typically outnumber men by 14 to 1 among those dying from natural disaster. Due to the scarcity of studies which document knowledge building on climate change among women particularly in flood-prone communities in Cotabato City prompted the researcher to conduct this study. Using an exploratory research design, 289 respondents were interviewed using questionnaires. Mean, frequency, and percentage were also utilized. Findings revealed that six out of seven women had heard about climate change and all have experienced its serious effects. Women had moderate knowledge on climate change. There was a significant difference in women’s knowledge when grouped according to age, educational attainment, and length of stay in the community. Women have some correct understanding of the issue yet they have misconceptions about the scientific causes and effects of climate change. Hence, the DepEd and CHED must ensure the integration of climate change and its full implementation in the basic education and the new tertiary general education curricula. This mechanism will ensure the building of knowledge and capacity of the youth on climate change.
Keywords: Climate change; flood-prone community; knowledge building; exploratory research design; Cotabato; Philippines